The development and ecology of the Japanese macaque gut microbiome from weaning to early adolescence in association with diet. Issue 10 (7th May 2019) - Prince, Amanda L.; Pace, Ryan M.; Dean, Tyler; Takahashi, Diana; Kievit, Paul; Friedman, Jacob E.; Aagaard, Kjersti M.
Abstract: Previously we have shown that the Japanese macaque gut microbiome differs not by obesity per se, but rather in association with high‐fat diet (HFD) feeding. This held true for both pregnant dams, as well as their 1‐year‐old offspring, even when weaned onto a control diet. Here we aimed to examine the stability of the gut microbiome over time and in response to maternal and postweaning HFD feeding from 6 months of age, and at 1 and 3 years of age. In both cross‐sectional and longitudinal specimens, we performed analysis of the V4 hypervariable region of the 16S rRNA gene on anus swabs collected from pregnant dams and their juveniles at age 6 months to 3 years ( n  = 55). Extracted microbial DNA was subjected to 16S‐amplicon‐based metagenomic sequencing on the Illumina MiSeq platform. We initially identified 272 unique bacterial genera, and multidimensional scaling revealed samples to cluster by age and diet exposures. Dirichlet multinomial mixture modeling of microbiota abundances enabled identification of two predominant enterotypes to which samples sorted, characterized primarily by Treponema abundance, or lack thereof. Approximating the time of initial weaning (6 months), the Japanese macaque offspring microbiome underwent a significant state type transition which stabilized from 1 to 3 years of age. However, we also found the low abundance Treponema enterotype to be strongly associated with HFD exposure, be it during gestation/lactation or in the postweaning interval. Examination of taxonomic co‐occurrences revealed samples within the low Treponema cluster were relatively permissive (allowing for increased interactions between microbiota) whereas samples within the high Treponema cluster were relatively exclusionary (suggesting decreased interactions amongst microbiota). Taken together, these findings suggest that Treponemes are keystone species in the developing gut microbiome of the gut, and susceptible to HFD feeding in their relative abundance. Research Highlights: Maternal diet structures the postnatal gut microbiome in Japanese macaques. The Japanese macaque gut microbiome communities are distinguished by the relative abundance of Treponema, largely as a consequence of permissivity versus exclusivity of other taxa. Major transitions in the gut microbiome occur postweaning likely due to cessation of nursing.